Is a river alive? - Macfarlane, Robert, 1976- (W.W. Norton & Company, 2025)
"Hailed in the New York Times as "a naturalist who can unfurl a sentence with the breathless ease of a master angler," Robert Macfarlane brings his glittering style to a profound work of travel writing, reportage, and natural history. Is a River Alive? is a joyful, mind-expanding exploration of an ancient, urgent idea: that rivers are living beings who should be recognized as such in imagination and law. Macfarlane takes readers on three unforgettable journeys teeming with extraordinary people, stories, and places: to the miraculous cloud-forests and mountain streams of Ecuador, to the wounded creeks and lagoons of India, and to the spectacular wild rivers of Canada--imperiled respectively by mining, pollution, and dams. Braiding these journeys is the life story of the fragile chalk stream a mile from Macfarlane's house, a stream who flows through his own years and days. Powered by dazzling prose and lit throughout by other minds and voices, Is a River Alive? will open hearts, challenge perspectives, and remind us that our fate flows with that of rivers--and always has." --